European electricity prices in times of multiple crises - Mathias Mier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
European energy crisis has three elements: skyrocketing prices for energy carriers such as natural gas, coal, as well as electricity, reduced nuclear power plant availability in France, and lower hydro power generation in Europe. This paper decomposes the effects of those elements on power markets and the EU ETS. Permanently higher natural gas prices reduce the canceling volume in the MSR by 425 million and prevent gas-CCS from being competitive in the long-run. Electricity prices are almost unaffected because gas-CCS is substituted by similarly competitive nuclear. Half of the 2022 European electricity price increase can be traced back to higher energy prices (from 36 to 143 e/MWh), whereas the other half (from 143 to 247 e/MWh) comes from French nuclear and European hydro problems. The decision to stretch the operation of three German nuclear power plants to counteract against those crises brings down European (German) electricity prices by 0.89% (2.47%) in 2023. Extending them for seven years after stretching, starting from September 2023, brings down electricity prices by 1.88% (4.8%) in 2024.
Keywords: C61; H21; H23; L94; Q41; 330; Electricity prices; natural gas prices; coal prices; nuclear power; hydro power; EU ETS; market stability reserve; power market modeling; intertemporal optimization